2007
DOI: 10.1002/mus.20844
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of fatigue differ after low‐ and high‐force fatiguing contractions in men and women

Abstract: The magnitude of failure in voluntary drive after fatiguing contractions of different intensities in men and women is not known. The purpose of this study was to compare the time to task failure and voluntary activation of men and women for a sustained isometric contraction performed at a low and high intensity with the elbow flexor muscles. Nine men and nine women sustained an isometric contraction at 20% and 80% of maximal voluntary contraction (MVC) force until task failure during separate sessions. The men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
132
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 48 publications
(73 reference statements)
18
132
2
2
Order By: Relevance
“…Furthermore, low-force contractions, which were sustained for longer durations than high-force tasks, involve greater fatigue originating from the central nervous system and upstream of the motor cortex, particularly in older adults [32,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low-force contractions, which were sustained for longer durations than high-force tasks, involve greater fatigue originating from the central nervous system and upstream of the motor cortex, particularly in older adults [32,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…We further expected that the MVC force decline immediately after task failure would be considerably less than 50% of MVC, even though the sustained contraction was performed at 50% MVC force; in other words, there would still be a reserve in muscle maximal force-generating capacity at the point of task failure. Second, as it has previously been shown that peripheral impairments were more pronounced after high-force-contraction tasks (10,50), whereas central alterations were found to increase with task duration (7,50,78), we hypothesized that, despite a similar decrease in MVC force for the different muscle groups, the relative contribution of central and peripheral mechanisms would be mainly determined by the duration of the sustained contraction.…”
mentioning
confidence: 92%
“…17,43,49 for discussion), and it can only indicate the presence of central fatigue and not its cause or location in the CNS (49). The extent to which central or peripheral mechanisms of fatigue are involved in the reduction in maximal torque-generating capacity depends on a number of factors, including contraction intensity (20,56), whether the contractions are sustained or intermittent (12), the muscle group used (10), and the age and/or sex of the subjects (26,32). In short, fatigue is task dependent (22).…”
mentioning
confidence: 99%
“…Specifically, during prolonged contractions (sustained or intermittent) at a low fraction of the MVC torque (ϳ5-30% MVC), the extent of central fatigue is substantial (47,48,56) and significantly greater than that during contractions at higher fractions of the MVC (20). In contrast, when submaximal contractions are performed at relatively high intensities (greater than ϳ30% MVC), peripheral fatigue is substantial (10,25,45), and central fatigue is either modest (20,56) or absent (10). However, it is not known whether the transition in fatigue processes between low-intensity and high-intensity contractions occurs gradually as the torque requirements are increased, or whether this transition occurs suddenly at some identifiable "threshold".…”
mentioning
confidence: 99%
See 1 more Smart Citation